Genomic analysis, evolution and characterization of the heat shock protein-70 gene family in foxtail millet [Setaria italica (L.) P.Beauv.] along with expression analysis under saline conditions - Jawad Ali; Ali Raza; Muhammad Aakif Khan; Aqib Zeb; Maliha Ghaffar; Maqsood Ahmed Khaskheli (International Journal of Applied and Experimental Biology)
Under stress conditions, heat shock proteins (HSPs) serve as fundamental regulators of cellular homeostasis. The molecular chaperone HSP70 belongs to a group of stress-related proteins which play important roles across growth and developmental events. The production of HSP70 proteins significantly increases during stress events including heat exposure, and salinity and drought conditions to protect proteins and maintain crucial macromolecular structures, thereby improving overall plant stress tolerance. This study identified 28 HSP70 genes in Setaria italica through phylogenetic analysis and placed these genes into four separate clades. The preserved structural elements and functional domains and conserved sequence patterns indicated that HSP70 genes maintain evolutionary stability. The HSP70 gene family spanned nine chromosomal scaffolds and most protein products were predicted to function in the cytoplasm. The analysis of synonymous substitutions and non-synonymous substitutions showed that HSP70 genes underwent both purifying and positive selection processes leading to their functional divergence. This study outcomes deliver a significant understanding of HSP70 genes' functional roles together with their association with plant growth and developmental processes.